PENGARUH KEADILAN ORGANISASI TERHADAP KEPUASAN KERJA DAN KEINGINAN KELUAR KARYAWAN PADA ALILA MANGGIS HOTEL KARANGASEM BALI - Suta, Arya Wira; Supartha, I Wayan Gede (E-Jurnal Manajemen, 2016)
The purpose of this study was to determine the effect of organizational justice on job satisfaction and desire out of employees at the hotel Alila Manggis, Karangasem, Bali. This research was conducted on employees Alila Manggis Hotel. Samples taken as many as 97 employees of Alila Manggis Hotel. The sampling technique random sampling, data collection was done by distributing questionnaires using a 5-point Likert scale to measure 30 item statement. The analysis technique used is the Path anaylsis. The results showed that the Justice organization and significant negative effect on the desire out. Second, Justice organization and significant positive effect on job satisfaction. Third, job satisfaction and significant negative effect on the desire out. The implications that may occur from this study is that the hotel could improve oversight and maintain a level of organizational justice and job satisfaction of employees for lowering the level of desire out of its employees